Modern examples of road and railway bridges illustrating the most recent practice of leading engineers in Europe and America - Maw, William H. (Engineering, 1872)
Bridges of the Severn Valley Railway, hydraulic swing bridges, the Czernowitz Bridge, the Singapore Suspension Bridge, the Bridge of El-Kantara, the Morlaix Viaduct and the Clifton Suspension Bridge are just some of the bridges described.